Analisis Kaidah Qashr dalam Surah Taha dan Penerapannya dalam Tafsir Ayat: Kajian Balaghah Al Qur’an - Assajad, Anas; Nugroho, kharis (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2024)
Ma'ani science is a branch of balaghah science. One of the discussions in ma'ani science is qashr, namely specializing something from something else in a certain way. There are two main pillars in qashr, namely maqshur and maqshur 'alaih. Judging from its main pillars, qashr is divided into 2, namely qashr alam 'ala maushuf and qashr maushuf 'ala alam. Based on the nature and reality, qashr is divided into 2, namely qashr haqiqi and qashr idhafi. There are 4 adatul qashr, namely, Nafyi (Exclusion) and Istitsna' (Exception), Lafadz Innamaa (إنما), using 'Athaf (combined letters), namely the letters: لا (not), بل (but) or لكن (but), and prioritize the lafadz that should be finished. This research uses descriptive analysis methods and includes library research. This research analyzes the text of the verses in Surah TaHa which contain qashr rules in them. This research found 17 sentences containing qashr rules contained in the TaHa letter. The 17 rules are summarized in 15 verses. Of the 17 qashr, 4 qashr function as takhshis, 8 function as ta'kid, 2 function as hashr, 1 function as tasliyah and 1 function as mubalaghah.